Differences in Short-Term Memory Who Listen to Music and Those Who Don't Listen to Music in Students of the Faculty of Medicine, University of Muhammadiyah North Sumatra - Naufal Adriansyah Damanik; Mila Trisna Sari (Buletin Farmatera, 2026)
Abstract: Short-term memory has an important role in cognitive function, especially in the process of learning and remembering information in a short period of time. One of the external factors that is often associated with memory abilities is music. A number of studies have found that music can improve focus and memory, but there are also studies that show that music can actually interfere with concentration. This difference in results became the basis for a study to find out whether there was a difference in short-term memory between the group that listened to music and the group that did not listen to music in students of the Faculty of Medicine, University of Muhammadiyah North Sumatra. The study used a quantitative approach with a quasi-experimental post-test with control group design and was analyzed using an independent t-test. The results showed a significant difference between the two groups. The average short-term memory score for students who listen to music is 9.6486, while for students who do not listen to music is 6.3784 with a p-value of 0.001. These findings suggest that listening to music can have a positive effect on short-term memory improvement, especially when the music chosen is in accordance with individual preferences and supported by memorization practice.